Postnephrectomy outcomes following en bloc resection of primary retroperitoneal sarcoma: multicentre study. Issue 2 (27th October 2021) - Fairweather, Mark; Lyu, Heather; Conti, Lorenzo; Callegaro, Dario; Radaelli, Stefano; Fiore, Marco; Ng, Deanna; Swallow, Carol; Gronchi, Alessandro; Raut, Chandrajit P.
Abstract : This article reports on postoperative renal function in the largest series of patients with primary retroperitoneal sarcoma undergoing nephrectomy at three high-volume sarcoma centres. Although half of patients develop chronic kidney disease of stage 3 or higher, rarely do patients develop acute renal failure requiring renal replacement therapy.